Severe eosinophilic colitis caused by neuropathic agents in a patient with chronic fatigue syndrome and functional abdominal pain: case report and review of the literature - Fragkos, Konstantinos C.; Barragry, John; Fernando, Charisma Shahi; Novelli, Marco; Begent, Joanna; Zárate-Lopez, Natalia (Zeitschrift für Gastroenterologie, 2018)
Eosinophilic colitis is a rare clinical condition that belongs to the group of eosinophilic gastrointestinal disorders. Its occurrence can be primary or secondary to infection, medications, or autoimmune/hematological conditions. We present a case of a young female adult with severe chronic fatigue syndrome, widespread chronic pain, including functional abdominal pain, who developed severe eosinophilic colitis following successive treatments with gabapentin and pregabalin. On both occasions, symptoms manifested as abdominal pain, diarrhea, and eosinophilia and improved upon discontinuation of the medications. Magnetic resonance imaging of the small bowel demonstrated an ascending colon colitis, and endoscopic investigations confirmed florid colitis mainly in the ascending colon with biopsies demonstrating a dense eosinophilic infiltrate with micro-abscesses. Serum eosinophil counts correlated well with the timing of the agents’ administration. There was no other organ involvement. Symptoms improved upon discontinuation of the drugs and steroid administration. Eosinophilic colitis is an exceptionally rare entity and its mechanism of action is still unclear. Suspicion of eosinophilic colitis should be raised if a patient presents with abdominal pain, diarrhea, and peripheral eosinophilia following treatment with pregabalin or gabapentin.
Keywords: gabapentin; pregabalin; eosinophilic colitis; myalgic encephalopathy; functional bowel disorder